The Effect of Men's Body Attitudes and Motivation for Gym Attendance. Issue 9 (September 2016) - Caudwell, Kim M.; Keatley, David A.
Abstract : Abstract: Caudwell, KM and Keatley, DA. The effect of men's body attitudes and motivation for gym attendance. J Strength Cond Res 30(9): 2550–2556, 2016—The current study integrates men's body attitudes with implicitly and explicitly measured motivation to investigate the role of these factors in predicting gym attendance. Male participants ( N = 99) who regularly attended a gym were recruited to participate in an online questionnaire. Participants completed implicit and explicit measures of motivation, explicitly measured men's body attitudes, and reported the average number of gym visits per week. Attitudes related to body fat and explicitly measured autonomous motivation significantly predicted typical gym attendance. Implicitly measured motivation significantly and negatively predicted gym attendance. Results indicate some support for a dual-systems account of gym attendance. Men's body attitudes and autonomous motivation influences gym attendance; however, implicitly measured motivation showed antagonistic effects. Although individuals may explicitly state their autonomous motivation for gym attendance, attendance may also be influenced at the explicit level. Health and fitness professionals may improve gym attendance by focusing on people's reasons for attending a gym, facilitating autonomous motivation in clients, and minimizing the influence of controlled reasons for exercise.